(untitled) (Ustozlar uchun, 2026)
A step-by-step prosthetic approach is used to enhance the quality of life for individuals who have had extensive maxillofacial oncological surgery. Over the last several decades, face prosthetics have advanced significantly due to the creation of materials that closely resemble biological tissues. Among these well-known substances are siloxanes. Silicone prosthesis are physiologically inert, retain their form, and do not lose their elasticity or durability, according to experimental and clinical research done by the Central Research Institute of Prosthetics. At the moment, this sector is actively incorporating 3D modelling and fast prototyping technology.